Energy Management of Distributed Generation Systems 2016
DOI: 10.5772/62923
|View full text |Cite
|
Sign up to set email alerts
|

Securing the Home Energy Management Platform

Abstract: Energy management in households gets increasingly more attention in the struggle to integrate more sustainable energy sources. Especially in the electrical system, smart grid systems are envisioned to be part in the efforts towards a better utilisation of the energy production and distribution infrastructure. The Home Energy Management System (HEMS) is a critical infrastructure component in this endeavour. Its main goal is to enable energy services utilising smart devices in the households based on the interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Literature around the design and development of HEMS is new and shaping up. Mikkelsen and Jacobsen [33] investigated HEMS and identified various threats to HEMS data, and key data flows that could happen between various stakeholders. Saha et al [40] identified possible attacks and their countermeasures.…”
Section: Hems Features and Functionalitiesmentioning
confidence: 99%
“…Literature around the design and development of HEMS is new and shaping up. Mikkelsen and Jacobsen [33] investigated HEMS and identified various threats to HEMS data, and key data flows that could happen between various stakeholders. Saha et al [40] identified possible attacks and their countermeasures.…”
Section: Hems Features and Functionalitiesmentioning
confidence: 99%